Spatial analysis, decision support systems (DSS) and land use design: the case-study of antique viability system in San Martino valley (Lombardy, Italy) - Andrea Cerizza; Giovanni Rabino (European Regional Science Association (ERSA), 2004)
This paper concerns the development of a Decision Support System (DSS), which is a system able to support temporal and spatial choices about land use design, in order to project and manage the antique viability system in San Martino valley (located in Lombardy, Italy) The main purpose is providing to a project manager necessary information to help him to understand problems (in particular concerning the spatial system of viability), therefore assists him to analyze the question from different points of view. This process needs a particular informative architecture, based on a complex and relational structured system (DSS) able to produce response for the whole decision process. The DSS is interfaced with a GIS in order to manage cartography and alphanumeric files with geo-referenced data. It works on information which are supposed to be indispensable for the planners of the San Martino valley.
Keywords: 330